Conformational Changes and Catalytic Competency of Hydrolases Adsorbing 1 on Fumed Silica Nanoparticles: I. Tertiary Structure - Cruz, Juan C.; Pfromm, Peter H.; Tomich, John M.; Rezac, Mary E. (My University, 2010)
We have recently introduced an immobilization protocol for preparations of enzymes on fumed silica for catalysis in organic solvents. The observation of a maximum in apparent catalytic activity at intermediate surface coverage for one enzyme while another enzyme showed continuously increasing apparent catalytic activity with decreasing surface coverage led to speculation on the impact of surface coverage on apparent catalytic activity through different relative surface-protein and protein-protein interactions, combined with different “hardness” or resistance towards unfolding by the enzymes. The kinetics of tertiary unfolding of Candida antarctica Lipase B (CALB), subtilisin Carlsberg, and the Lipase from Thermomyces lanuginosus (TLL) adsorbing on fumed silica nanoparticles were inferred here from tryptophan fluorescence for 2%SC to 1250%SC, 0.5 mg/mL to 4.70 mg/mL enzyme concentration in aqueous buffer solution, and in the presence of the structural modifiers 2,2,2-trifluoroethanol (TFE) and Dithiothreitol (DTT). The results shown here confirm the earlier speculation that “hard” enzymes can perform well at low and intermediate surface coverage of the solid fumed silica particles until multi-layer packing imposes mass transfer limitations, while “soft” enzymes unfold at low surface coverage and therefore show a maximum in catalytic competency at intermediate surface coverage before declining apparent activity is caused by multi-layer packing.
Keywords: Conformational stability; Adsorption; Fumed Silica; CALB; TFE; DTT